The analysis of self-government entity’s budget expenditure in Poland over years of 2004–2009 - Kamba-Kibatshi, Marcel (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
Undoubtedly, the budget is the basis of independent financial economy of the local government, especially including commune. The budget expenses of the self-government are an expression of public tasks accomplishment which commune is obliged to fulfill. The purpose of the article is to present analysis (evaluation) of local government budget expenses and their influence on the commune development in years 2004–2007, in order to realized – what the scale of expenses was in different communes in Poland. Increasing range of accomplished tasks by the self-government, including the necessity of accomplishing running tasks on the determined level, causes that local government units more and more often are appearing on the capital market, by contracting credits or issuing bonds.

Niewątpliwie podstawą samodzielnej gospodarki finansowej samorządu terytorialnego a w szczególności gminy jest jej budżet. Wydatki budżetu samorządu terytorialnego są wyrazem realizacji zadań publicznych, do wykonywania których zobowiązana jest wspólnota gminna. Omawiany artykuł miał na celu przedstawienie analizy (oceny) wpływu wydatków budżetu samorządu terytorialnego na jego rozwój w latach 2004–2007, by obrazowo zorientować się – jaka skala wydatków występowała w różnych gminach w Polsce. Rosnący zakres realizowanych zadań przez samorząd, w tym także konieczność realizacji zadań bieżących na określonym poziomie powoduje, że jednostki samorządu terytorialnego coraz częściej występują na rynku kapitałowym zaciągając kredyty, czy emitując obligacje.